The role of administrative transparency in reducing administrative corruption in Libyan public institutions from the point of view of the employees of the National Anti-Corruption Authority in the region (Sebha University Conference Proceedings, 2022)
This study aimed to identify the role played by administrative transparency in reducing administrative corruption in Libyan public institutions from the point of view of the employees of the National Anti-Corruption Authority in the southern region. It also tries to find out whether there are elements of administrative transparency in it. This study works to identify the effects of administrative corruption on public institutions in the southern region. The data for the study was collected through a questionnaire, which included (50) items, The statistical program (SPSS) was used to process the data statistically. The study concluded that administrative transparency in Libyan public institutions is low, which may greatly help administrative corruption. It also found the need to work with administrative transparency to reduce administrative corruption. Accordingly, the study concluded that Libyan public institutions should work to improve administrative transparency in them by ensuring the provision of sufficient information to all relevant parties and working to put in place strong regulations and laws that would be a warning to those who violate them. It also led to the establishment of clear and known standards for all; to facilitate the accountability process, facilitate work procedures and make them clearer.